Fatigue, Stress, and Job Satisfaction in the Air Traffic Controller (ATC) Work - Atmaka, Ekky Widha (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the relationship between fatigue, stress, and job satisfaction among Air Traffic Controllers (ATCs). ATCs often experience physical and mental fatigue due to irregular work schedules, frequent shift changes, and high workload. Fatigue is defined as a state of exhaustion that affects alertness and decision-making abilities, increasing the risk of errors. Factors such as lack of sleep, time pressure, and the need to coordinate with multiple parties exacerbate stress. The research also shows that job satisfaction, which is crucial for psychological well-being, is influenced by levels of fatigue and stress. Low job satisfaction leads to burnout and reduced motivation, negatively impacting air traffic management. However, factors such as adequate rest, a supportive work environment, and fair compensation enhance job satisfaction. A quantitative research method was used, employing tools like the Fatigue Assessment Scale (FAS), Samn-Perelli 7-Point Scale, and Karolinska Sleepiness Scale. The results indicate that workload and stress are the main contributors to fatigue, with stress peaking during heavy air traffic periods. ATCs with higher job satisfaction demonstrated better stress-coping mechanisms. Recommendations include fatigue risk management programs, improved shift planning, adequate rest facilities, and psychological support. This study provides insights into the importance of mitigating fatigue and stress to enhance job satisfaction and operational safety.